INTERACTIVE METHODS AND METHODS OF THEIR APPLICATION IN THE DEVELOPMENT OF CREATIVE ABILITIES OF SCHOOLCHILDREN IN MUSIC TRAINING. (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
in this article, the school in music sessions consists of theoretical foundations of the methodology of application of interactive methods and methods of their application in the development of students ' creative abilities.